MR Urography In Pediatric Population: A Real Assessment (Nepalese Journal of Radiology, 2012)
Various conditions affecting the pediatric genitourinary system can be assessed with Radiography, Ultrasound,Computed tomography, Nuclear Medicine and Magnetic Resonance Imaging. Imaging modalities based on the use of ionizing radiation are a big drawback in this patient group. Magnetic resonance imaging offers a big advantage in this regard. MR urography (MRU) represents the next step in the evolution of genitourinary imaging in children by combining visualization of great anatomic details with functional evaluation of the kidneys .Adequate patient immobilization coupled with rapid imaging sequences allows acquisition of high-quality images. In the future, MRU is expected to become the most important diagnostic tool in genitourinary imaging in pediatric age group. NJR I VOL 2 I ISSUE 1 67-69 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6987